ANALISIS PENGARUH VARIABEL MAKRO EKONOMI TERHADAP KINERJA KEUANGAN PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Damayanti, Ganis Dwiky; Abdullah , Mohammad Faisal; Hariyani, Happy Febrina (Program Studi Ekonomi Pembangunan, 2021)
This research aims to determine effect of macroeconomic variables consisting of inflation, interest rates, and exchange rates on the financial performance of food and beverage company issuers on the Indonesia Stock Exchange. Moreover, the financial variable was measured by Return On Equity (ROE). The population in this research is the issuers of the food and beverage company on the Indonesia Stock Exchange during the period 2016-2020 that is as many as 27 issuers. The sample selection is done by using purposive sampling method and obtained a sample of 19 issuers. This research uses panel data regression. The results of the research concluded that macroeconomic variables consisting of inflation, interest rates, and exchange rates Simultaneously, had a significant effect on company performance. Partially inflation and exchange rates have a significant negative effect. Meanwhile, interest rate have no significant negative effect on the financial performance of companies in the food and beverage company issuers on the Indonesia Stock Exchange